Focused Evidence-Based Medicine Curriculum for Trainees in Neonatal-Perinatal Medicine - Mohan Pammi; Krithika Lingappan; Melissa M. Carbajal; Gautham K. Suresh (Association of American Medical Colleges, 2017)
Introduction While evidence-based medicine (EBM) is an Accreditation Council for Graduate Medical Education core competency, EBM teaching in pediatric subspecialties is rarely reported. Therefore, we designed, implemented, and evaluated this focused EBM curriculum for trainees in neonatal-perinatal medicine. Methods This EBM curriculum consists of seven weekly 1-hour sessions. Specific EBM skills taught in the sessions include formulating a structured clinical question, conducting an efficient literature search, critically appraising published literature in both intervention and diagnostic studies, and incorporating evidence into clinical decision-making. The course was evaluated by a neonatology-adapted Fresno test (NAFT) and neonatology case vignettes, which were administered to learners before and after the curriculum. This publication includes the needs assessment survey, PowerPoint slides for the seven sessions, the NAFT, and the scoring rubric for the test. Results The NAFT was internally reliable, with a Cronbach's alpha of .74. The intraclass correlation coefficient of the three raters' variability in assessment of learners was excellent at .98. Mean test scores increased significantly (54 points, p < .001) in 14 learners after the EBM curriculum, indicating an increase in EBM-related knowledge and skills. Discussion This focused EBM curriculum enhances trainees' knowledge and skills and fosters evidence-based practice. The curriculum can be easily adapted for learners in pediatrics, as well as family medicine, in order to enhance trainees' EBM skills and knowledge.